The effects of progressive muscle relaxation and autogenic relaxation on young soccer players` mood states - Hashim, H. A.; Hanafi, H.; Yusof, A. (Asian Journal of Sports Medicine, 2011)
Purpose: This study was designed to compare the effects of two different relaxation techniques, namely progressive muscle relaxation (PMR) and autogenic relaxation (AGR) on moods of young soccer players. Methods: Sixteen adolescent athletes (mean age: 14.1 ± 1.3) received either PMR or AGR training. Using Profile of Mood States-Adolescents, their mood states were measured one week before relaxation training, before the first relaxation session, and after the twelfth relaxation session. Results: Mixed ANOVA revealed no significant interaction effects and no significant main effects in any of the subscales. However, significant main effects for testing sessions were found for confusion, depression, fatigue, and tension subscales. Post hoc tests revealed post-intervention reductions in the confusion, depression, fatigue, and tension subscale scores. Conclusions: These two relaxation techniques induce equivalent mood responses and may be used to regulate young soccer players' mood states.